(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research aims to develop an elderly-friendly city model for Bangkok, Thailand, focusing on addressing the challenges of an aging society by holistically enhancing the quality of life for the elderly. The study is guided by four main objectives: (1) to examine the current state of elderly quality of life and city development conducive to aging populations, (2) to identify city development factors influencing elderly quality of life, (3) to design and develop an elderly-friendly city model, and (4) to validate the developed model through expert evaluation. A mixed-methods approach was employed. Quantitative data was collected from 400 elderly participants across six pilot districts in Bangkok, while qualitative data was obtained through in-depth interviews and the Delphi technique. Findings indicate that the overall quality of life among the elderly is at a “high” level (mean = 4.21), with environmental and psychological dimensions scoring the highest. However, limitations remain in areas such as income, sleep, and social engagement. According to the WHO criteria for elderly-friendly cities, five districts were rated “very good,” while Suan Luang District was rated “good.” Key weaknesses identified include housing and economic participation. Positive factors contributing to elderly quality of life include social acceptance, access to information, and community support. Conversely, negative factors include inadequate housing and limited social participation. The proposed model integrates the eight domains of the WHO elderly-friendly framework with the principles of Active Ageing and Universal Design. It emphasizes five strategic directions: (1) enhancing elderly-friendly public transportation systems, (2) promoting safe and accessible housing, (3) expanding opportunities for social and economic participation, (4) developing inclusive communication systems for all age groups, and (5) fostering local partnerships to ensure sustainable implementation. This model can serve as a prototype for other cities aiming to adapt effectively to an ageing society with quality of life at its core.